2012
DOI: 10.12669/pjms.291.2566
|View full text |Cite
|
Sign up to set email alerts
|

Current pattern of antibiotic resistance of clinical isolates among conjunctival swabs

Abstract: Objectives: To identify the etiological agent in bacterial conjunctivitis and to determine the antibiogram of bacterial isolates. Methodology: This observational study was conducted at Dr. Essa’s Laboratory over a period of 12 months ending in March 2012. Two hundred samples taken from conjunctiva of patients with conjunctivitis were cultured on routine medium and the antibiograms of bacterial isolates were determined by Kirby- Bauer disc diffusion method. Results: The analysis of the culture showed that 41% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…Staphylococcal isolates were predominant among patients with conjunctivitis, blepharitis and blepharoconjunctivitis diagnoses, similar to that in patients from Jimma [6], Nigeria [23], and Columbia [48]. Conversely,, CoNS isolates were more frequent in keratitis (17%) and endophthalmitis (28.6%) diagnoses, as has been reported in Uganda [49], Mexico [50], Australia [8], Pakistan [51] and India [52]. …”
Section: Discussionsupporting
confidence: 71%
“…Staphylococcal isolates were predominant among patients with conjunctivitis, blepharitis and blepharoconjunctivitis diagnoses, similar to that in patients from Jimma [6], Nigeria [23], and Columbia [48]. Conversely,, CoNS isolates were more frequent in keratitis (17%) and endophthalmitis (28.6%) diagnoses, as has been reported in Uganda [49], Mexico [50], Australia [8], Pakistan [51] and India [52]. …”
Section: Discussionsupporting
confidence: 71%
“…In Individuals with underlying disease such as diabetic mellitus and rheumatoid arthritis, the diminished immunity may result in loss of control of systemic infections with subsequent spread to ocular tissues especially in endophthalmitis [ 62 , 71 ]. This has also been evidenced in case of K. pneumoniae endophthalmitis infections and M. catarrhalis keratitis infections [ 72 , 73 ] In addition, age might be a factor due to waning immunity and susceptibility to bacterial ocular infections [ 13 , 74 ]. Operative procedures, prophylactic measures and topical use of corticosteroids are also good predisposing factors for bacterial ocular infections associated with the immune suppression and inability to kill some organisms like P. aeruginosa and S. epidermidis [ 12 , 59 ].…”
Section: Discussionmentioning
confidence: 94%
“…In the New York Eye and Ear Infirmary, Adebayo and colleagues reviewed 12 years of data from their hospital and found that, among 20,180 conjunctival bacterial cultures, 60.1% were culture-positive and S. aureus was the most common pathogen; in addition, moxifloxacin and gatifloxacin currently appear to be the best choice for empirical broad-spectrum coverage [ 7 ]. Additionally, other reports on the ocular bacterial infection and antibiotic susceptibility have been reported in the literature from various countries, like Colombia [ 8 ], Pakistan [ 9 ], Italy [ 10 ], and Uganda [ 11 ], among other locations.…”
Section: Introductionmentioning
confidence: 99%